Treponeme-Associated Hoof Disease of Free-Ranging Elk (Cervus elaphus) in Southwestern Washington State, USA. Issue 1 (January 2019) - Han, Sushan; Mansfield, Kristin G.; Bradway, Dan S.; Besser, Thomas E.; Read, Deryck H.; Haldorson, Gary J.; Alt, David P.; Wilson-Welder, Jennifer H.
A novel foot disease in free-ranging elk ( Cervus elaphus ) in southwestern Washington State emerged in 2008 and spread throughout the region. Initial studies showed adult elk had chronic hoof overgrowth, sole ulcers, and sloughed hoof capsules, but no cause was determined. To identify possible causes and characterize the earliest lesions, 9-, 7-, and 3-month-old elk were collected. Nine-month-old elk had sole ulcers (3/9 elk) and sloughed/overgrown hoof capsules (4/9 elk) similar to adults. Histologically, lesions consisted of coronary, heel bulb, and interdigital ulcers with suppurative inflammation, epithelial hyperplasia, deeply invasive spirochetes, and underrunning of the hoof capsule and heel-sole junction. Spirochetes were identified as Treponema via immunohistochemistry and polymerase chain reaction (PCR). Seven-month-old elk had similar underrunning foot ulcers (6/8 elk) with Treponema identified in all lesions but no chronic overgrowth or sloughed hoof capsules. Three-month-old calves had superficial coronary erosions with no inflammation or identifiable spirochetes (3/5 elk) but were culture/PCR positive for Treponema, suggesting possible early lesions. Lesions from 9- and 7-month-old elk included aerobic and anaerobic bacteria, many of which are associated with infectious foot disease in livestock. Antibody enzyme-linked immunosorbent assay of 7- and 3-month-old elk from the enzootic region showed a trend toward increased Treponema antibody titers compared to normal control elk from outside the region, further supporting the significance of Treponema in the pathogenesis of foot disease. Treponeme-associated hoof disease (TAHD) in elk, a debilitating and progressive condition, shares similarities to bovine digital dermatitis and contagious ovine digital dermatitis.